Human, conceptual and technical skills as determinants of preservation management in university libraries in Southern Nigeria (2018)
Purpose – Preservation is an essential component of library management that requires special skills and competencies. This critical area seems to have been neglected by management of university libraries in Nigeria. This paper aims to examine threats to library information resources and contributions of skills of library personnel to preservation management in university libraries. Design/methodology/approach – Descriptive survey design was adopted for the study. This facilitated the collection of data from large population of respondents. Questionnaire and focus group discussion were used as data collection instruments. Findings – Preservation management is one of the core areas of library practice that requires special skills. The study revealed that university libraries in Nigeria are confronted with threats to their information resources. The study found that human, conceptual and technical skills of library personnel significantly determine preservation management in university libraries in Southern Nigeria. Practical implications – The paper will allow the management of university libraries to appreciate the importance of personnel skills as the key factor for effective preservation management in libraries and accord it the necessary priority. Originality/value – While literature is replete with different aspects of preservation management in university libraries in Africa, little has been written on personnel skills and preservation management in libraries. The paper presents one of the few empirical studies that focus on the relationship between personnel skills and preservation management in university libraries in Nigeria and Africa.